An Overview of the Sociological and Environmental Factors Influencing Eating Food Behavior in Canada - Marcone, Massimo F.; Madan, Pavneesh; Grodzinski, Bernard (Frontiers in Nutrition, 2020)
This review extensively discusses various socio environmental factors affecting eating behavior of the general public within Canada including the development and implementation of national policies. A framework representing the determinants of healthy eating can be grouped into four categories i.e., the individual determinants, the economic environment, the social environment and the physical environment. This framework allowed for addressing food insecurity and social economic ecosystem of Canadians. Lastly, we investigate the role in which biotechnology plays in improving food security and addresses the significant impact biotechnology has contributed toward on agriculture and the food market. Overall, this review using such sources as Web of Science, Pub Med and Scopus provides significant contribution toward understanding the social economic environment and eating behavior of people living in Canada. In conclusion, this has led to identify a research gap as there is a significant need to address the development and implementation of policies in the food and nutrition environment.